2016
DOI: 10.1038/pr.2016.183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four commercial virological assays for early infant HIV-1 diagnosis using dried blood specimens

Abstract: CVAs using DBS were useful for EID, although discrepant results were common. Further research is required to reduce false-positive results that could result in wrong diagnosis and unneeded treatment. We propose caution with low viral load (VL) values when using VL assays. Clear guidelines are required for EID of HIV-exposed infants with discrepant virological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Nurses in two primary healthcare centres performed the collection of the cobas 1 PSC specimens for this study, attesting to the feasibility of implementing this new method in resourcelimited health systems. The procedures for collecting cobas 1 PSC specimens are similar to those for DBS, which health professionals throughout sub-Saharan Africa have been using in HIV viral load testing and early infant diagnosis for many years [6,[8][9][10]. Additionally, in this study viral load testing using cobas 1 PSC specimens was executed in a laboratory that routinely tests for viral load and early infant diagnosis, with no additional equipment required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses in two primary healthcare centres performed the collection of the cobas 1 PSC specimens for this study, attesting to the feasibility of implementing this new method in resourcelimited health systems. The procedures for collecting cobas 1 PSC specimens are similar to those for DBS, which health professionals throughout sub-Saharan Africa have been using in HIV viral load testing and early infant diagnosis for many years [6,[8][9][10]. Additionally, in this study viral load testing using cobas 1 PSC specimens was executed in a laboratory that routinely tests for viral load and early infant diagnosis, with no additional equipment required.…”
Section: Discussionmentioning
confidence: 99%
“…Whole capillary or venous blood is spotted onto filter paper cards to prepare DBS. This method of whole blood collection has been very successfully implemented for diagnosing HIV-infection among infants younger than 18 months through the qualitative detection of HIV-1 proviral DNA [8][9][10]. The comparative advantages of DBS include their ease of transportation, lack of cold chain needs and low biosafety requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported discordant or false‐positive values using molecular technologies, either qualitative or quantitative assays . While there is a correlation between the cycle threshold value and the level of virus in a sample, the various circulating viral subtypes, assay techniques, and use of older technologies can led to discordant PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of four commercial virological assays for early infant HIV-1 diagnosis using dried blood specimens, these tests were all useful for EID, although discrepant results were common [16]. These studies advocate further research to reduce false-positive results that could lead to false diagnosis and unnecessary treatment, and that caution should be exercised in interpreting the results of quantitative PCR with low viral load (VL) values and in developing guidelines for the management of cases with discordant virological findings [15,16].…”
Section: What Early Diagnosismentioning
confidence: 99%